Perceptions of Medical Errors in Cancer Care: An Analysis of How the News Media Describe Sentinel Events. Issue 1 (March 2015) - Li, Justin W.; Morway, Laurinda; Velasquez, Andrew; Weingart, Saul N.; Stuver, Sherri O.
Abstract : Objective: To analyze the print news media's coverage of sentinel events involving cancer patients. Methods: Using LexisNexis ®, we identified English-language newspaper articles covering medical errors in cancer care between January 1, 2000, and December 31, 2010. Articles were coded for 3 major themes using a standardized abstraction instrument: narrative statements and point of view most prominently represented, attribution of blame, and orientation toward patient safety. We also abstracted country where the newspaper was published, type of error event, and extent of patient harm. Results: We analyzed 64 articles from 37 print newspaper syndications that circulated in 6 countries/regions. Reports of medical errors rarely were framed from the point of view of a safety expert or the responsible clinician (13% and 3%, respectively) compared with the patient and legal points of view (both 30%). Articles held individual clinicians (41%) and hospital systems (28%) responsible for most errors. Four in 10 articles failed to present medical errors as "systems" problems. Article perspective varied considerably by country, with 53% of articles from the UK and 63% from Australia and New Zealand judged as negatively slanted compared with 14% in the United States and Canada. Conclusions: In reports of medical errors involving cancer patients, the news media regularly blame individual clinicians for mistakes and fail to present a systems-based understanding of these events.